How Normal Meat Becomes Stranger as Cultured Meat Becomes More Normal; Ambivalence and Ambiguity Below the Surface of Behavior - van der Weele, Cor; Driessen, Clemens (Frontiers in Sustainable Food Systems, 2019)
Although the majority of people still behave like happy meat eaters, there are good reasons to think that many are in fact ambivalent about meat. Following up on earlier findings, in this paper we describe how, in focus groups, cultured meat triggered much discussion about meat, especially among older people. While young people wondered whether they would eat cultured meat products, older people thought about diet changes in a historical perspective and wondered if and how cultured meat might become a societal success. Beneath the surface of everyday behaviour, in which they followed mainstream norms, many of our research participants harboured moral concerns and in various ways expressed an interest in collective change. Reflecting on the focus group discussions, we suggest, first, that appreciating the important role of ambivalence in processes of moral change requires rethinking relations between ambivalence and morality. Second, the entanglement of ambivalence with ambiguity increases the ‘fluidity’ of such processes of change: when it is no longer clear what exactly meat is, the meanings and experiences of eating it also become unsettled. This has implications for thinking about morality in times of change. Studying consumer choices cannot do justice to processes of ambivalence and ambiguity below the surface of behaviour. More generally, the idea that morality resides in making up our minds about clear moral choices gives way to the need to become skilled, collectively as well as individually, in dealing imaginatively with ambivalence and ambiguity.